An Effect of Electrical Current Strength and DCEN Polarity on SMAW Welding Results in Butt Joint Position 1G - Veronika, Rika; Bohari, Bohari; Putra, Ananda Yhuto Wibisono (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2023)
This study aims to understand the effect of current strength variations on the Direct Current Negative Electrode (DCEN) polarity on the results of welding at butt joint joints. In this study, ASTM A36 steel was chosen as the main material, while the E6013 electrode was used as the welding electrode. The method used is an experimental approach with a qualitative approach, which allows researchers to gain a deeper understanding of the effect of current variables on welding results. The results of three experiments conducted at welding current of 60 A, 90 A, and 120 A provide a clear picture of the effect of these variables on the butt joint. In the first specimen with a current strength of 60 A, there was not enough penetration and many defects in the capping. Low current strength does not produce optimal welding results at the joint. However, in the second specimen with a current strength of 90 A, there was an initiation of penetration, although it was still incomplete. There are also fewer defects in the capping compared to the first specimen, and it shows an increase in welding results with an increase in current strength. In the third specimen with a current strength of 120 A, there is better penetration, but still not achieving complete penetration. In addition, the capping has many defects, including the suck back. It shows that using high current strength only sometimes produces optimal welding results and can present challenges, such as joint defects.